ANALISIS NETWORK PLANNING REPARASI KAPAL FLAMINGO AWB 3377GT DENGAN METODE CRITICAL PATH METHOD - Asta Nusa Abdul Aziz (2021)
Network planning or also known as network planning is a model used in the implementation of ship repair projects. The network planning analysis method applied to the repair of the AWB Flamingo 3377 GT ship uses the CPM (Critical Path Method) method. The purpose of getting this is for network planning on ship repair work so that there are no delays and to find out which activities are critical paths to minimize delays in completing ship repairs. The type of research used is descriptive qualitative and quantitative research. The research variables used are the creation of a network, allowing the earliest time of occurrence of an event (EET)and the slowest time of occurrence of an event (LET), critical path and completiontime of ship repair projects. From the results of this study, it can be seen that the results of network planning in ship repair projects using the CPM method found 11critical activations/activities, namely pre docking, water jet & fresh water rinse, sandblasting hull, trash bin, frame and 1 ton bracket , welding fittings, ultra sonic test, painted hull (bottop) to top side, checking & repairing, and post docking. By using CPM, the difference in the completion time is 17 days, while the previous duration of completion was 20 days. For comparison, the price of the CPMmethod is greater than the previous calculation, which is Rp. 5,000,000 (five million rupiah)